Gone to Texas : a history of the Lone Star State - Campbell, Randolph B., 1940- (Oxford University Press, 2003)
Tells the story of the Lone Star State from the arrival of humans in the Panhandle more than 10,000 years ago to the opening of the 21st Century. Focusing on the state's successive waves of immigrants, it offers an inclusive view of the array of Texans who, often in conflict with each other and the land, created a history and an idea of Texas.